An electrochemical approach for tryptophan detection that regulates the kynurenine pathway - Pavithra Narasimhappa; Praveen C. Ramamurthy (Scientific Reports)
Abstract An electrochemical sensor for detecting tryptophan (Trp) was developed through the electro-polymerization of a phenazinium chloride derivative/safranin (SA) on both a glassy carbon electrode (GCE) and a screen-printed electrode (SPE). The sensor’s electrochemical properties were assessed using cyclic voltammetry (CV), with a focus on optimizing various parameters such as the pH of the supporting electrolyte, the scan rate, the SA concentration for polymerization, and the number of CV cycles. The significant decrease in the energy bandgap of Trp in the presence of SA provides strong evidence for enhanced electron transfer efficiency. The results demonstrated that the electrochemical oxidation of Trp is predominantly a diffusion-controlled and irreversible process. A linear relationship was observed between the anodic oxidation peak and the Trp concentration, ranging from 10 to 90 µM. Detection and quantification limits were determined to be 2.3 µM and 7.8 µM for the SA/GCE configuration, and 1.17 µM and 3.9 µM for the SA/SPE configuration, respectively. The modified electrodes displayed exceptional selectivity, stability, and reproducibility. Their practical utility was further validated in tests involving bovine serum albumin, where the sensor achieved outstanding detection performance.